2013
DOI: 10.1016/j.neulet.2013.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of spontaneous regeneration of olfactory structures with emphasis on myelination and re-innervation of cortical areas

Abstract: Regeneration of the lateral olfactory tract (LOT) occurs spontaneously after transection in developing rats. In neonatally LOT-transected rats, we observed a newly-formed myelinated tract near the rhinal sulcus. The aim of this study was to analyze the precise re-innervated cortical areas and to demonstrate ectopic LOT myelination in neonatally LOT-transected rats. Neonatal rats were subjected to unilateral LOT transection and simultaneous injection of a retrograde fluorescent tracer into the posterior olfacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…LOT transection was performed in P2 pups (n = 70) unilaterally on the left side, as described previously [11][12][13]. Briefly, the LOT was transected at the posterior half of the olfactory stria by inserting the tip of a knife (Ophthalmic Scleral MVR Knife, 25 gauge; Alcon, Tokyo, Japan) from the ventrolateral aspect of the head.…”
Section: Lot Transection and Retrograde Tracer Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…LOT transection was performed in P2 pups (n = 70) unilaterally on the left side, as described previously [11][12][13]. Briefly, the LOT was transected at the posterior half of the olfactory stria by inserting the tip of a knife (Ophthalmic Scleral MVR Knife, 25 gauge; Alcon, Tokyo, Japan) from the ventrolateral aspect of the head.…”
Section: Lot Transection and Retrograde Tracer Injectionmentioning
confidence: 99%
“…The lateral olfactory tract (LOT) is the main fiber tract of the central olfactory system and exclusively consists of myelinated axon fibers. We have recently demonstrated that the neonatally transected LOT can be replaced by newly-formed axon fibers connecting the olfactory bulb and the olfactory cortex (the olfactory tubercle and piriform cortex) via the transected site at a later stage [11][12][13][14]. Because the regenerated LOT is primarily composed of unmyelinated axon fibers, LOT injury is a good animal model to examine the effects of ALC on myelin formation in the developing brain.…”
Section: Introductionmentioning
confidence: 99%